Une activité potière du viie siècle au 20 rue de la République à Vanves (Hauts-de-Seine) - Étienne Jaffrot; Antoine Nadeau (Revue Archéologique du Centre de la France)
The pottery kiln discovered at the 20 rue de la République, Vanves (92), gives us new datas concerning this area of craftsmanship, in activity from the early Roman Empire to the carolingian period at least (as brought to light by four Inrap excavations from 1999 to 2005). A short term stratigraphic sequency, that occured in the end of the 7th century according to radiocarbon and ceramologic datations, gather information about how the kiln was built, how it worked and when it was abandoned. The ceramic study is based on the PCR and ICéramm procedures. This study gives us a picture of a little pottery production and a representative ceramic assemblage from Île-de-France. Furthermore, two ceramic lamps are exceptional finds.